Dynamic changes in hepatitis C virus genotypes and sequence patterns in plasma donors exposed to reinfection - Zhang, Shu-min; Hui, Zhuang; Li, He-min; Qi, Zi-bai; Widell, Anders (Journal of medical virology, 2001)
Sequential serum samples from four plasma donors (designated A, B, C, and D) at a Chinese blood bank with hepatitis C transmission problems were studied from 1994 to 1997. The samples were examined for antibodies to HCV, for HCV viremia by PCR and HCV genotyping. Co‐ and superinfections were studied by direct sequencing of the 5′‐NCR, core, and HVR‐1 regions, using low and high genotype‐specific primers targeting the HVR‐1, and by cloning of selected samples. Genotype changes occurred in all four donors: A (1b‐2a‐1b), B (1b‐2a‐2a/1b‐1b), C (1b‐2a), and D (1b/2a‐1b). Donor D was married to donor B. The 1b isolates of donor A could not be sequenced in the HVR‐1 due to low‐level viremia. Two early 1b isolates from donors B and C showed high HVR‐1 similarity. The later 1b isolates from B had changed significantly but were identical to the isolate from donor D. Spouses B and D also shared genotype 2a strains. The 2a isolates from donors A, B/D, and C differed by 8–10 nucleotides in the HVR‐1. The frequent changes in genotype and the appearance of homologous isolates from different subjects indicate transmission at the blood bank. These four donors, all identified shortly after infection, developed very few mutations in the HVR‐1 and few quasispecies during a period of 6–18 months. Highly specific primers proved to be superior to cloning for identification of minor virus populations. The results indicate nosocomial transmission of more than one strain at the blood bank studied. J. Med. Virol. 63:228–236, 2001. © 2001 Wiley‐Liss, Inc.